Community Composition and Phytochemical Constituents of Rheum australe D. Don in Rasuwa District, Nepal - Pandit, Rajani; Paudel, Babu Ram; Chaudhary, Ram Prasad; Pyakurel, Dipesh; Rajbhandari, Meena; Subedi, Chandra Kanta (Himalayan Biodiversity, 2025)
Rheum australe (Himalayan Rhubarb), a medically significant perennial herb, is endemic to the Himalayan region. This paper evaluates the population status and phytochemical composition of R. australe in the Rasuwa District of Nepal, along an elevation range from 3,300 m asl to 3,800 m asl. For the study, sixty quadrats of size 2 m × 2 m were studied to assess the community characteristics such as density, frequency, and importance value index (IVI). Also, hexane, ethyl acetate and methanol extracts of the rhizome from the plant was taken and the phytochemical screening was performed. Phenolics and flavonoids content, antioxidant activity, and antibacterial properties were evaluated. The results for population status indicated that R. australe flourishes in east-facing slopes in between 40-50° at higher altitudes ranging from 3,700m-3,800 m asl. Also, the population status was significantly influenced by altitude and disturbance levels (p < 0.05). The result indicated that the methanolic extract showed higher amounts of phenolic content and antioxidant activity, while ethyl acetate extract exhibited superior flavonoid content and antibacterial efficacy against Escherichia coli, Klebsiella pneumoniae, Bacillus subtilis, and Staphylococcus aureus.